Enhancing Elementary School Students’ Understanding of the Nature of Science and their Environmental Awareness through Ethnoscience-Based E-Worksheets - Wulan Octi Pratiwi; Ulfah Umurohmi; Winda Cicilia (JIP Jurnal Ilmiah PGMI, 2025)
The Nature of Science (NoS) and Environmental Awareness (EA) are fundamental components in fostering scientific thinking and responsible environmental behavior. However, previous studies indicate that elementary students’ understanding of both aspects remains low. Science instruction in schools often emphasizes memorization, and existing worksheets are generally conventional and lack integration of ethnoscience, connecting cultural practices with scientific concepts. This gap highlights the need for culturally relevant digital learning materials. The novelty of the study lies in the development and evaluation of a validated ethnoscience-based E-Worksheet designed to enhance students’ NoS and EA through contextualized and meaningful learning experiences. The study analyzed the effect of E-Worksheet on elementary students in Bandar Lampung, following expert validation. Data were obtained from 30 purposively selected students whose schools implemented the E-Worksheet, meeting the minimum sample requirements for the Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis conducted using SmartPLS 4. The analysis obtained an R² value of 0.778, indicating that the ethnoscience-based E-Worksheet simultaneously affects students’ NoS and EA. These findings demonstrate that validated ethnoscience-integrated digital worksheets can effectively strengthen scientific reasoning and environmental responsibility in elementary education, emphasizing the importance of incorporating culturally relevant digital materials into science learning. The findings were supported by validated NoS and EA questionnaires developed through literature review and expert judgment.